Molecular and Cellular Mechanisms Modulating Trained Immunity by Various Cell Types in Response to Pathogen Encounter - Acevedo, Orlando A.; Berrios, Roslye V.; Rodríguez-Guilarte, Linmar; Lillo-Dapremont, Bastián; Kalergis, Alexis M. (Frontiers in Immunology, 2021)
The induction of trained immunity represents an emerging concept defined as the ability of innate immune cells to acquire a memory phenotype, which is a typical hallmark of the adaptive response. Key points that are modulated during the establishment of trained immunity include epigenetic, metabolic and functional changes in different innate-immune and non-immune cells. With regards to epigenetic changes, it has been described that long non-coding RNAs (LncRNAs) act as molecular scaffolds to allow the assembly of chromatin-remodelling complexes that catalyze epigenetic changes on chromatin. On the other hand, relevant metabolic changes that occur during this process include increased glycolytic rate and the accumulation of metabolites from the tricarboxylic acid (TCA) cycle, which subsequently regulate the activity of histone-modifying enzymes that ultimately drive epigenetic changes. Functional consequences of established trained immunity include enhanced cytokine production, increased antigen presentation and augmented antimicrobial responses. In this article, we will discuss the current knowledge regarding the ability of different cell subsets to acquire a trained immune phenotype and the molecular mechanisms involved in triggering such a response. This knowledge will be helpful for the development of broad-spectrum therapies against infectious diseases based on the modulation of epigenetic and metabolic cues regulating the development of trained immunity.